Milk fed ebook A novel. - Broder, Melissa (2021)
Named a Best Book of the Year by Entertainment Weekly , Vogue , Time , Esquire , BookPage , and more This darkly hilarious and "delicious new novel that ravishes with sex and food" ( The Boston Globe ) from the acclaimed author of The Pisces and So Sad Today is a "precise blend of desire, discomfort, spirituality, and existential ache" ( BuzzFeed ). Rachel is twenty-four, a lapsed Jew who has made calorie restriction her religion. By day, she maintains an illusion of existential control, through obsessive food rituals, while working as an underling at a Los Angeles talent management agency. At night, she pedals nowhere on the elliptical machine. Rachel is content to carry on subsisting—until her therapist encourages her to take a ninety-day communication detox from her mother, who raised her in the tradition of calorie counting. Rachel soon meets Miriam, a zaftig young Orthodox Jewish woman who works at her favorite frozen yogurt shop and is intent upon feeding her. Rachel is suddenly and powerfully entranced by Miriam—by her sundaes and her body, her faith and her family—and as the two grow closer, Rachel embarks on a journey marked by mirrors, mysticism, mothers, milk, and honey. "A ruthless, laugh-out-loud examination of life under the tyranny of diet culture" ( Glamour ) Broder tells a tale of appetites: physical hunger, sexual desire, spiritual longing, and the ways that we compartmentalize these so often interdependent instincts. Milk Fed is "riotously funny and perfectly profane" ( Refinery 29 ) from "a wild, wicked mind" ( Los Angeles Times ).